Studi Bibliometrik: Analisis Tren dan Pemetaan Pengetahuan Mikroplastik Serta Dampak Kesehatan di ASEAN: Studi Bibliometrik Berbasis Scopus (2019-2024) - Nisrinah, Nisrinah; Mushliha, Mushliha (Yayasan Literasi Sains Indonesia, 2025)
Plastic waste is a problem faced by various countries, especially ASEAN member countries. Microplastics are even more dangerous if they enter the food chain. Several studies have found microplastics in aquatic biota, which, if consumed by humans at certain levels, can harm health. In the ASEAN region, research related to microplastics is still limited despite the region having high levels of plastic pollution. This study seeks to investigate the interconnectedness of microplastic research in ASEAN through bibliometrics. Vosviewer was used for bibliometric studies to provide a comprehensive overview and identify future research directions based on past works in the Scopus database on microplastics. This study utilized 1,656 journal articles from the last five years, from 2019 to 2024, focusing on 10 ASEAN countries. The analysis results show that research is still dominated by studies of microplastic pollution and distribution in aquatic environments, with an emphasis on particle abundance. Although attention to aspects of toxicity, bioaccumulation, and human health implications is starting to increase, research integrating the physicochemical properties of microplastics with toxicological mechanisms and biological impacts is still limited. Furthermore, indicator organism-based biomonitoring approaches and comprehensive risk assessments have not been widely developed. Therefore, further research needs to focus on interdisciplinary approaches that link microplastic characteristics, adsorbed contaminants, and health impacts.